PENGUATAN KAPASITAS SANTRI DALAM KESIAPSIAGAAN BENCANA KEBAKARAN DAN PERTOLONGAN PERTAMA DI PONDOK PESANTREN MALAYSIA - Friska Ayu; Merry Sunaryo; Moch. Sahri; Nur Ainiyah; Catur Wulandari; Yauwan Tobing Lukiyono (Universitas Muhammadiyah Mataram, 2026)
Abstrak: Kebakaran di lingkungan pondok pesantren berpotensi menimbulkan kerugian besar karena tingginya aktivitas santri dan penggunaan instalasi listrik yang padat sehingga meningkatkan risiko korsleting. Santri sebagai kelompok rentan memerlukan penguatan kapasitas dalam kesiapsiagaan kebakaran dan pertolongan pertama. Program pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pengetahuan dan keterampilan santri dalam pencegahan kebakaran serta penanganan awal keadaan darurat di Pondok Pesantren Malaysia. Kegiatan dilaksanakan melalui sosialisasi interaktif, penyuluhan, simulasi pemadaman api menggunakan karung goni dan APAR, serta pelatihan pertolongan pertama menggunakan P3K kepada 33 santri dan pengurus pesantren sebagai mitra kegiatan. Evaluasi dilakukan melalui pre-test dan post-test untuk mengukur peningkatan pemahaman peserta terkait kesiapsiagaan penanganan kebakaran dan pertolongan pertama. Indikator keberhasilan keguatan ditetapkan berdasarkan peningkatan proporsi pengetahuan peserta yang mencapai kategori tinggi (16-20 jawaban benar), peningkatan nilai rata-rata skor pengetahuan dan analisis perbedaan skor sebelum dan setelah dilakukan intervensi menggunakan uji paired sample t-test. Hasil kegiatan menunjukkan peningkatan pengetahuan kesiapsiagaan kebakaran pada santri dari 15,2% menajdi 54,5% dengan rata-rata skor pengetahuan meningkat dari 11,2± 2,3 menjadi 15,6± 2,1 (p=0,008), sedangkan pengetahuan terkait P3K mengalami peningkatan dari 12,1% menjadi 51,5%, dengan rata-rata skor 10,8 ± 2,5 menjadi 15,1 ± 2,2 (p=0.0010). Selain itu, santri mampu melakukan simulasi evakuasi, penggunaan APAR dan melakukan pertolongan pertama menggunakan P3K secara mandiri sebagai bentuk penguatan mitigasi non-struktural di lingkungan pesantren.Abstract: Fire disasters in Islamic boarding schools have the potential to cause significant losses due to high student activity and intensive use of electrical installations, which increase the risk of short circuits. Santri as a vulnerable group require strengthened capacity in fire disaster preparedness and first aid management. This community service program aimed to improve the knowledge and skills of santri in fire prevention and emergency first aid management at an Islamic boarding school in Malaysia. The program was conducted through interactive socialization, health education, fire extinguishing simulations using burlap sacks and fire extinguishers (APAR), as well as first aid training using first aid kits for 33 santri and boarding school administrators as community partners. Evaluation was conducted using pre-test and post-test assessments to measure improvements in participants’ understanding of fire emergency preparedness and first aid management. The success indicators of the program were determined based on the increase in the proportion of participants achieving a high level of knowledge (16–20 correct answers), improvements in mean knowledge scores, and the analysis of score differences before and after the intervention using a paired sample t-test. The results demonstrated a significant improvement in students’ fire preparedness knowledge, with the proportion of participants in the high-knowledge category increasing from 15.2% to 54.5%. The mean knowledge score also increased from 11.2 ± 2.3 to 15.6 ± 2.1 (p = 0.008). Similarly, knowledge related to first aid (P3K) improved substantially, with the proportion of participants in the high-knowledge category increasing from 12.1% to 51.5%, while the mean score increased from 10.8 ± 2.5 to 15.1 ± 2.2 (p = 0.010). In addition, the students were able to independently perform evacuation procedures, operate portable fire extinguishers (APAR), and provide first aid using first aid kits (P3K). These outcomes indicate that the program successfully strengthened non-structural disaster mitigation efforts and enhanced emergency preparedness capacity within the Islamic boarding school environment.